2006
DOI: 10.1177/1740774506070807
|View full text |Cite
|
Sign up to set email alerts
|

Impact of on-site initiation visits on patient recruitment and data quality in a randomized trial of adjuvant chemotherapy for breast cancer

Abstract: Systematic on-site initiation visits did not contribute significantly to this clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 18 publications
0
48
0
Order By: Relevance
“…Two studies compared clinicians (nurses vs surgeons; community vs university medical practices) 23 30. Two studies assessed the effect of extra involvement of trial coordinators with clinicians (extra communication; on-site initiation visits) 24 25. One study assessed the effect of change to training and paying for protected research time on recruitment 29…”
Section: Resultsmentioning
confidence: 99%
“…Two studies compared clinicians (nurses vs surgeons; community vs university medical practices) 23 30. Two studies assessed the effect of extra involvement of trial coordinators with clinicians (extra communication; on-site initiation visits) 24 25. One study assessed the effect of change to training and paying for protected research time on recruitment 29…”
Section: Resultsmentioning
confidence: 99%
“…Excessive site monitoring was identified as a barrier to reform [3], although the conference-endorsed monitoring aimed at detecting procedural errors that could compromise patient safety or bias outcome data (essential for unblinded trials) [24]. Furthermore, the conference proposed that site monitoring should focus on training and enthusing staff, solving problems, assessing protocol adherence, and checking resources [24], all elements of the PRIME system. These wider aims for site monitoring were supported by results from the Women's Health Initiative trial, where sites with low staff turnover had higher follow-up rates [25].…”
Section: Discussionmentioning
confidence: 99%
“…Developments to tailor site monitoring to the needs of the trial based on the risks to patient safety and data are currently under investigation [12]. Techniques for remote statistical monitoring are also being developed [24] and are used by some academic trial units to replace site visits [15]. Intensive site monitoring systems can be costly [3,26], and a simulation model estimated that the costs of an industry-designed IMP trial could be nearly halved by reducing the CRF length and site monitoring frequency by up to 75% [27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized trial showed that systematic center initiation visits (without qualitative research) did not improve recruitment or randomization [14]. The centers reviewed in this study were fully compliant with Good Clinical Practice according to the audit of consent procedures, but the qualitative research identified aspects of study information and presentation that could be improved to ensure better informed consent and high levels of randomization.…”
Section: Box 3 Examples Of Poor Descriptions Of Randomizationmentioning
confidence: 96%